DAMPAK ARTIFICIAL INTELLIGENCE TERHADAP AKTIVITAS PUSTAKAWAN DALAM KEGIATAN LITERASI ONLINE SERIES - Bambang Hermanto; Masriyatun Masriyatun (Warta Perpustakaan Pusat Undip, 2024)
Abstract :This study was conducted with the aim of determining the impact of the application of Artificial intelligence in online information literacy activities at the UNS Library. Information literacy activities organized by the UNS Library for 7 months from January to July 2024 consisted of 15  activities.  The  number  of  information  literacy  participants  was  1,200  students.  The determination of the number of samples in this study used the Slovin formula and was taken using a simple random sampling technique of 92 people. The results of the study showed that there was  an impact  of Artificial intelligence on librarian activities in online  literacy series activities with a very high category of 22 people or 24.0%, high of 37 people or 40.2% and moderate of 28 people or 28.2%.  Keywords:  artificial  intelligence,  college  libraries,  information  technology,  information literacy, librarian activities Abstrak :Penelitian  ini  dilakukan  dengan  tujuan  untuk  mengetahui  dampak  penerapan  artifical intelligence  dalam  kegiatan  literasi  informasi  secara  online  di  UPT  Perpustakaan  UNS. Kegiatan literasi informasi yang diselenggarakan oleh UPT Perpustakaan UNS selama 7 bulan dari bulan Januari sampai Juli 2024 sebanyak 15 kegiatan. Jumlah peserta literasi informasi sebanyak  1.200  mahasiswa.    Penentuan  jumlah  sampel  dalam  penelitian  ini  menggunakan rumus slovin dan diambil menggunakan tehnik simple random sampling sebanyak 92 orang. Hasil  penelitian  menunjukan  ada  dampak  dari  artifical  intelligence  terhadap  aktivitas pustakawan dalam kegiatan literasi online series dengan kategori sangat tinggi 22 orang atau 24,0 %, tinggi sejumlah 37 orang atau 40,2 % dan sedang sejumlah 28 orang atau 28,2 %.Kata kunci :  artifical intelligence, perpustakaan perguruan  tinggi, teknologi informasi, litersi informasi, aktivitas pustakawan